2013
DOI: 10.1016/j.bmcl.2013.09.075
|View full text |Cite
|
Sign up to set email alerts
|

Discovery, design and synthesis of a selective S1P3 receptor allosteric agonist

Abstract: Potent and selective S1P3 receptor (S1P3-R) agonists may represent important proof-of-principle tools used to clarify the receptor biological function and assess the therapeutic potential of the S1P3-R in cardiovascular, inflammatory and pulmonary diseases. N,N-Dicyclohexyl-5-propylisoxazole-3-carboxamide was identified by a high-throughput screening of MLSMR library as a promising S1P3-R agonist. Rational chemical modifications of the hit allowed the identification of N,N-dicyclohexyl-5-cyclopropylisoxazole-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…To test that idea directly, the recently discovered selective agonist of S1PR 3 , CYM-5541, was used [ 25 ]. In Chinese hamster ovary cells (CHOs) stably expressing S1PRs, the half-maximal effective concentration (EC 50 ) values for CYM-5541 activation of S1PR 3 was 105 nM and for S1PR 1 it was approximately 33 μM, and there was no activity at S1PR 2/4/5 for concentrations as high as 50 μM [ 25 ]. We found that CYM-5541 in a time- and concentration-dependent manner lead to the sensitization of AP firing in small-diameter sensory neurons.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To test that idea directly, the recently discovered selective agonist of S1PR 3 , CYM-5541, was used [ 25 ]. In Chinese hamster ovary cells (CHOs) stably expressing S1PRs, the half-maximal effective concentration (EC 50 ) values for CYM-5541 activation of S1PR 3 was 105 nM and for S1PR 1 it was approximately 33 μM, and there was no activity at S1PR 2/4/5 for concentrations as high as 50 μM [ 25 ]. We found that CYM-5541 in a time- and concentration-dependent manner lead to the sensitization of AP firing in small-diameter sensory neurons.…”
Section: Resultsmentioning
confidence: 99%
“…After a 20-min washout with normal Ringers, the membrane potential had recovered by 40% ± 17% (range 4% to 82%). It is possible that this high concentration of CYM-5541 depolarizes the neuronal membrane through activation of S1PR 1 rather than R 3 as the EC 50 for CYM-5541 at S1PR 1 is approximately 33 μM [ 25 ]. To test this idea, sensory neurons were pretreated for 30 min with either 1 or 10 μM W146.…”
Section: Resultsmentioning
confidence: 99%
“…J-2156 was assessed in a lead profiling binding assay screen (Ricerca Biosciences LLC) consisting of 67 pharmacological targets, to identify the binding of J-2156 for a range of receptors, ion channels and transporters, by following standard radioligand binding assay protocols (Guerrero et al, 2010a , b ; Strøbæk et al, 2013 ). These included important targets like sodium ion channels because they are known to be involved in pain pathophysiology (Amir et al, 2006 ; Dib-Hajj et al, 2009 , 2010 ).…”
Section: Methodsmentioning
confidence: 99%
“…S1P was obtained from Avanti Polar. CYM-51736, is an allosteric agonist of S1PR 3 of the structure N,N-dicyclohexyl-5-(furan-3-yl)isoxazole-3-carboxamide [29, 30], was provided by Dr. Hugh Rosen (The Scripps Research Institute, La Jolla, CA).…”
Section: Methodsmentioning
confidence: 99%